TEOLOGI KEBUDAYAAN PADA RELIEF PURA DALÊM SANGSIT DESA SANGSIT KECAMATAN SAWAN KABUPATEN BULELENG - I Wayan Sunampan Putra; Ni Made, Yunitha Asri Diantary; Windya, Ida Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The purpose of this study is to study and analyze Pura Dalêm Kêlod Sangsit which has uniqueness in the form of symbols. Where in general Pura Dalêm is identical with scary things. However, Pura Dalêm Sangsit actually displays an erotic dimension. Departing from this gap, Pura Dalêm Kêlod Sangsit will be studied with cultural theology. The method used in this study is to use a qualitative research type with a cultural theology approach. The type of data is qualitative through the collection of observation data, interviews, and literature studies. Then analyzed using data analysis techniques. The results obtained are that Pura Dalêm Sangsit has a unique form of symbols that have erotic nuances, but erotic symbols as a cultural aspect not only have material aspects but also have spiritual and theological dimensions. So that there is a relationship between culture in the form of symbols with aspects of theology. From this, it can be concluded that the erotic symbols in Pura Dalêm Sangsit as a form of culture have theological meaning.